Pengaruh Sistem Tanam, Biaya Pemupukan dan Biaya Pestisida Terhadap Pendapatan Usahatani Padi Sawah di Kecamatan Birem Bayeun Kab. Aceh Timur - Hanisah; Rozaliana; M Sareza (Program Studi Agribisnis Fakultas Pertanian Universitas Samudra, 2019)
The aim of this research to know plant system, fertilizer cost, pesticide cost effected to revenue of paddy farm business Birem Bayeun sub-district East Aceh district. This research used survey method. Farmer sample in this research was 20% from a 150 person population and the sample was 30 farmer from each village. the analysis method used multiple linear regression. Result showed that plant system and pesticide cost weren’t effected. Meanwhile fertilizer cost was effected to revenue of paddy farm business in Birem Bayeun sub-district